Self‐adhesive plasticized regenerated silk on poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) for bio‐piezoelectric force sensor and microwave circuit design. Issue 4 (18th August 2020) - Bittolo Bon, Silvia; Valentini, Luca; Degli Esposti, Micaela; Morselli, Davide; Fabbri, Paola; Palazzi, Valentina; Mezzanotte, Paolo; Roselli, Luca
Abstract: This study shows that regenerated silk (RS), a natural biodegradable and biocompatible polymer, can behave as a self‐adhesive thermoplastic material with multifunctional properties. In particular, Ca ions‐plasticized RS hybrids with gold nanorods have been produced. It has been found that at mild conditions of temperature and pressure, RS hybrids undergo to the loss of the β‐sheet content and forms a tough self‐adhesive material on poly(3‐hydroxybutyrate‐ co ‐3‐hydroxyvalerate) (PHBV) substrate. The structure‐dependent piezoelectricity of such RS adhesives on PHBV films was investigated and it was demonstrated that this forms a RS/PHBV piezoelectric sensor that can be used for the monitoring of force. The constitutive parameters (i.e., permittivity and loss tangent) of both PHBV and RS/PHBV were measured in view of their use as dielectric substrates in microwave circuit design. Being fully made of biodegradable and biocompatible materials, this self‐adhesive material can be used in tissue engineering for different applications. Abstract :